Resilience in the Historic Center of Lima. Social micro intervention in the solar El Jaime - Pittman Cortez, Silvia (2016)
The case study is rooted in the workshop named Generating Resiliency in Barrios Altos, where groups composed of students and professionals from different disciplines were assembled to analyze different quintas in order to propose low cost interventions with high impact. In the El Jaime solar, located in Barrios Altos, about 41 families have been living for many years suffering poverty, affected by the deficient physical state of the property, which involves water systems, drainage and electrical wiring. Among all these shortcomings, one of the urgent needs of the solar was the implementation of stairs that enable a quick and safe evacuation in the eventuality of a natural disaster, so to prevent harm from coming to its users. To achieve its implementation, we developed an intervention which involved various internal and external actors. Hand in hand with different professional and technical advisors, a participation methodology in conjunction with the community was organized.